Analisa Faktor-Faktor yang Mempengaruhi Proses Belajar Guru-Guru Sekolah Dasar - Anugraheni, Indri (Kelola: Jurnal Manajemen Pendidikan, 2017)
The purpose of this research is to know and describe factors influencing elementary school teachers in Biak Numfor District, and efforts made by elementary school teachers of Biak and suggestions for the development of education especially in Biak Numfor District. The method used in this research is descriptive. The research subjects were elementary school teachers in Biak Numfor District. Data obtained by distributing instrument in the form of Questionnaire. The results of a questionnaire that was distributed to 31 elementary school teachers in Biak Numfor district showed that many of the obstacles experienced by teachers. Obstacles experienced by elementary school teachers in Biak Numfor district are teachers experiencing obstacles in preparing the lesson, teachers experience barriers in determining methods and media used in learning, teachers experience barriers in determining the evaluation used in learning. Efforts by teachers to overcome these obstacles are many students who do not have a handbook then the teachers, and teachers use the media in school. Teachers hope the attention of local governments need to be improved again.